Effects of bio-fertilizers and nano-silicon on phosphorus uptake, grain yield and some physiological traits of wheat (Triticum aestivum L.) under withholding irrigation conditions - Farnaz Ahmadi Nouraldinvand; Raouf Seyed Sharifi; Seyed Ataollah Siadat; Razieh Khalilzadeh (تنش های محیطی در علوم زراعی, 2023)
IntroductionDrought is assumed as one of the most severe abiotic stress factors limiting plant growth and crop production. Since in arid and semi-arid regions, some part of growth period of wheat is confronted with water limitation condition which can affect biochemical and physiological responses such as changes in photosynthetic efficiency of PSII, chlorophyll content, and stomatal conductance. Application of bio fertilizers and silicon is one of the most important strategies for alleviation of drought stress effects. Bio fertilizers (plant growth promoting rhizobacteria or PGPR and mycorrhiza) can improve plant performance under non-stress and stress conditions. Thererfore, it seems that application of nano silicon and bio-fertilizer can improve wheat yield under water limitation conditions.Materials and methodsIn order to study the effects of biofertilizers and nanosilicon on phosphorus uptake, grain yield, and some physiological traits of wheat (Triticum aestivum L.) under withholding irrigation conditions, a factorial experiment was carried out at the research farm faculty of Agriculture and Natural Resources, University of Mohaghegh Ardabili, with three replications during 2018-2019. The area is 38° 15′ N latitude, 48° 15′ E longitude, and 1350 m above mean sea level. Climatically, the area is situated in the semi-arid temperate zone with a cold winter and moderate summer. Factors were included irrigation in three levels (full irrigation as control; moderate water limitation or withholding irrigation at 50% of the heading stage; severe water limitation or withholding irrigation at 50% of the booting stage) based on codes 55 and 43 of the BBCH scale; foliar application of nano silicon (foliar application with water as control, 30 and 60 mg.L-1) and bio-fertilizer (no application as control, mycorrhiza application, both application of flavobacterium and pseudomonas, both application of flavobacterium and pseudomonas with mycorrhiza). Mycorrhiza fungi (mosseae) was purchased from the Zist Fanavar Turan Corporation and soils were treated based on method of Gianinazzi et al. (2001). Psedomunas and flovobacterium were isolated from the rhizospheres of wheat by Research Institute of Soil and Water, Tehran, Iran. For inoculation, seeds were coated with gum Arabic as an adhesive and rolled into the suspension of bacteria until uniformly coated. The strains and cell densities of microorganisms used as PGPR in this experiment were 1×108 colony forming units (CFU). In this study, electrical conductivity, stomatal conductance, leaf fluorescence parameters, phosphorus of root and grain, relative water content, electrolyte leakage, anthocyanins and grain yield of wheat were investigated. Analysis of variance and mean comparisons were performed using SAS ver 9.1 computer software packages. The main effects and interactions were tested using the least significant difference (LSD) test at the 0.05 probability level.Results and discussionThe results showed that application of both flavobacterium and pseudomonas with mycorrhiza and foliar application of 60 mg.L-1 nano silicon under severe water limitation increased 84.32%, 49% and 49.52% of electrolyte leakage, electrical conductivity and minimum fluorescence (F0) respectively, and decreased root and grain phosphorus by 30.67 and 36.05% compared to full irrigation. The highest RWC (92.26%), stomatal conductance (58.86 mmol.m-2.s), anthocyanin (0.0274 µmol.g-1FW), Fm (860), and Fv/Fm (0.909) were obtained at foliar application of 60 mg.L-1 nano silicon, both applications of flavobacterium and pseudomonas with mycorrhiza under normal irrigation. Also, the highest grain yield was obtained with both flavobacterium and pseudomonas with mycorrhiza and foliar application of 30 mg.l-1 nano silicon under normal irrigation. According to the results of this study both the application of biofertilizers and nanosilicon can improve wheat grain yield under water limitation conditions by improving the physiological traits and also the uptake of phosphorus from the soil.ConclusionGenerally, it seems that application of bio fertilizers and nano silicon can be recommended as the proper method for increasing the physiological trait grain yield of wheat under water limitation conditions.